Noun and verb codes in English monolingual dictionaries for foreign learners: A study of usefulness in the Polish context - Dziemianko, Anna (Wydawnictwo Naukowe UAM, 2012)
The book is devoted to noun and verb coding systems in monolingual dictionaries for foreign learners of English. It opens with an overview of noun and verb codes in learners’ dictionaries published in the years 1938–2010. Tracing the evolution of coding systems for the two parts of speech throughout the history of English pedagogical lexicography leads to the identification of two approaches to coding the syntax of nouns and verbs. Mainstream and alternative coding systems are distinguished, and it is they that inspired the empirical study presented in the next part of the book. Around 900 native speakers of Polish took part in the experiment conducted to assess the usefulness of the identified systems of codes. Besides the subjects’ proficiency in English, the following variables were included: degree of syntactic congruence between English and Polish lexical items, presence of codes, form of codes and part of speech. The participants were given a test in which they had to complete partial English translations of 12 Polish sentences using specific nouns and verbs in appropriate syntactic constructions. The nouns and verbs were headwords of dictionary entries compiled for the purpose of the study and manipulated accordingly. The obtained results make it possible to judge whether syntactic codes in learners’ dictionaries are necessary, how their user-friendliness is affected by the selected variables and whether the global character of pedagogical dictionaries of English should be changed, considering syntactic anisomorphism between English and users’ native language. Apart from codes, attention is paid to examples, the other vehicle for syntactic information in the supplied entries.
496 stron
Keywords: codes; nouns; verbs; dictionaries; dictionary use; syntax; learners' dictionaries; user-friendliness; usefulness